CORRELATION OF ORGANIZATIONAL CULTURE AND WORK ENVIRONMENT WITH EMPLOYEE PERFORMANCE - Trisninawati, Trisninawati; Chantika, Trievanni; Sartika, Dewi; Helmi, Sulaiman; Sahrani, Shafrida (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This study aims to analyze the impact of organizational culture and work environment on employee performance, with job satisfaction as a mediating variable, at Information and Communication Technology Company. The background of the study stems from observed issues such as declining employee performance, high absenteeism, and inequality in facilities and organizational policies. Using a quantitative method with a causal-explanatory design, data were collected from 94 randomly selected employees through a structured questionnaire and analyzed using the Partial Least Squares Structural Equation Modeling (SEM-PLS) approach. The results show that both organizational culture and work environment significantly influence job satisfaction, which in turn mediates their effect on employee performance. Additionally, organizational culture and work environment each have a direct positive impact on performance. These findings emphasize the critical psychological role of job satisfaction in linking organizational conditions with productivity outcomes. The implication of this study is that companies, particularly in the ICT sector, can enhance employee performance by developing a strong organizational culture and improving both physical and social aspects of the work environment in a strategic and sustainable manner.